2020
DOI: 10.1111/andr.12922
|View full text |Cite
|
Sign up to set email alerts
|

Rectification of cavernosal fibrosis and veno‐occlusive dysfunction by administration of suberoylanilide hydroxamic acid in a rat model of cavernosal nerve injury: Comparison with a PDE5 inhibitor

Abstract: Background Cavernosal fibrosis, which is induced by cavernosal nerve (CN) injury and progresses with time, is the main cause of cavernosal veno‐occlusive dysfunction (CVOD) after radical prostatectomy. Objectives To determine whether daily oral administration of suberoylanilide hydroxamic acid (SAHA; vorinostat) for 5‐weeks from the immediate post‐injury period after CN injury would rectify CVOD by suppressing cavernosal fibrosis and normalizing HDAC pathway in a rat model of CN crush injury (CNCI) and to comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…There are no previous data regarding the effects of an HDAC inhibitor, NaBu on the erectile function in obstructed rats. However, chronic administration of other HDAC inhibitors improved the erectile function by suppressing cavernosal fibrosis in a rat model of cavernosal nerve injury 27,28 . Penile erection is mediated by nitric oxide (NO) produced by eNOS and nNOS 29 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are no previous data regarding the effects of an HDAC inhibitor, NaBu on the erectile function in obstructed rats. However, chronic administration of other HDAC inhibitors improved the erectile function by suppressing cavernosal fibrosis in a rat model of cavernosal nerve injury 27,28 . Penile erection is mediated by nitric oxide (NO) produced by eNOS and nNOS 29 .…”
Section: Discussionmentioning
confidence: 99%
“…However, chronic administration of other HDAC inhibitors improved the erectile function by suppressing cavernosal fibrosis in a rat model of cavernosal nerve injury. 27,28 Penile erection is mediated by nitric oxide (NO) produced by eNOS and nNOS. 29 We found that decreased nNOS protein expression in the PBOO group was ameliorated by NaBu treatment.…”
Section: Tnf-α Levels In the Penile Tissue Of Ratsmentioning
confidence: 99%
“…In a recent study, we showed that the administration of HDACi significantly improved CVOD in a rat model of CNCI. 17 HDAC11), but the differences in their roles have not been clearly identified. SAHA, the HDACi we used in this study, inhibits both class I and II of HDAC.…”
Section: Discussionmentioning
confidence: 99%
“…For CN crush injuries (mechanical compressions), a microsurgical vascular clamp was applied to the CN 4 ‐ 5 mm distal to the bilateral major pelvic ganglions (MPGs) for 80 s, removed for 30 s, then reapplied for an additional 80 s. In the J group, 10 mg/kg of JNKi (SP600125, Selleckchem, USA) was injected intraperitoneally once a day, and saline vehicle was orally administered 15 . The H group received oral administration of 25 mg/kg of HDACi (SAHA, Vorinostat, Selleckchem, USA) once daily and daily intraperitoneal injection of saline vehicle 17 . The J+H group was administered a combination of 10 mg/kg JNKi and 25 mg/kg HDACi.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation